Soluble sugars and mineral nutrient contents in kernels of three Tunisian almond cultivars - Ben Mohamed H.; Mselmi Taoueb S.; Zrig A.; Ben Hamda H.; Harbi Ben Slimane M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond is an important food crop grown mainly in the Mediterranean region and the USA. The kernel is the edible part of the nut and is considered a rich source of many nutrients. In the present study, total soluble sugars and mineral nutrient contents were quantified in the kernel of three local Prunus dulcis (Mill.) D.A. Webb cultivars selected from Tunisia. Cultivars are from three different origins. ‘Tozeur 1’ is from the south (Tozeur region), ‘Achaak’ is from the centre (Sfax region) while ‘G25-5’ is from the north (Mornag region). Mineral composition was analyzed by atomic absorption spectrometer and the amount of Mg, K, Na, Ca, Fe, Zn, Cu and Mn was determined. Among mineral nutrients, K, Ca and Mg were the predominant elements in kernels. Moreover, potassium (K) was the major mineral element for which amounts up to 683 mg/100 g (dry matter). ‘Achaak’ had higher Ca level (234.6 mg/100 g), however, there was no significant difference in K and Mg contents between three studied cultivars. Total soluble sugar contents showed difference among cultivars and the highest value (5.7 g/100 g) was found in ‘G25-5’ kernels. So, the obtained results showed that almond kernels are being potential sources of mineral elements which might be used as useful dietary supplements. Additionally, results of this study may provide relevant data for future studies on the chemical composition and will be useful to know about the nutritional properties of the local almond kernels.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)